Work System Improvement in the Production Process Station Area PT SMS Using Macro Ergonomics and Design (MEAD) to Increase Productivity - Heri Setiawan; Sani Susanto; Micheline Rinamurti; Achmad Alfian; Yohanes Dicka Pratama; Dominikus Budiarto (Ann Publisher, 2025)
Background. PT SMS produces bottled drinking water (amdk) in gallons and cups with Vit and Forme brands for gallon packaging and Airnes, Forma, and OK Oce brands in cup packaging. In identifying the problem at PT SMS, it was found that the work system is not well-designed and lacks ergonomics at several workstations, which has an impact on achieving less than optimal daily productivity. The output per work shift set by the company is 2,100 gallons and 3,150 boxes for cup packaging, but in fact, it can only produce approximately 2,050 gallons and 3,000 boxes. Aim. Analyze the factors that cause the work system to be less effective and less ergonomic. The formulation of work system factors encompasses physical work environment factors, equipment, infrastructure, machinery, workload factors, and organisational factors. Methods. The Macro Ergonomic Analysis and Design (MEAD) method is used to identify factors that affect the work system and then implement improvements and design changes based on the identified factors. Results. Physical work environment factors and organisational factors are problems within the work system at PT SMS, as the workspace designated for the production workflow lacks ergonomic support for employees' postures while working, and task management is inadequate. The machinery has not been crafted based on the anthropometric measurements of the workers. Oversight is absent for the work being done, and the standard time required for the production process has yet to be established. So that it increases productivity per work shift at PT. SMS is not optimal and experiences over time. Conclusions. Redesign of physical work environment facilities, scheduling of rest periods, and organisational factors through supervision from PT SMS resulted in output per shift meeting the standards set by the company.. Implication. The application of MEAD can identify factors that cause suboptimal productivity. Redesigning ergonomic physical work environment facilities, scheduling rest periods, and supervisory organisational factors within the company have an impact on optimising productivity, as measured by the output per shift set by the company